Portuguese Consensus on the Diagnosis and Management of Lewy Body Dementia (PORTUCALE) - Monteiro, A (2020)
Lewy body dementia is a common cause of dementia leading to the progressive deterioration of cognitive function and motor skills, behavioral changes, and loss of autonomy, impairing the quality of life of patients and their families. Even though it is the second leading cause of neurodegenerative dementia, diagnosis is still challenging, due to its heterogenous clinical presentation, especially in the early stages of the disease. Accordingly, Lewy body dementia is often misdiagnosed and clinically mismanaged. The lack of diagnostic accuracy has important implications for patients, given their increased susceptibility to the adverse effects of certain drugs, such as antipsychotics, which may worsen some symptoms associated with Lewy body dementia. Therefore, a specialist consensus based on the analysis of the most updated and relevant literature, and on clinical experience, is useful to all professionals involved in the care of these patients. This work aims to inform and provide recommendations about the best diagnostic and therapeutic approaches in Lewy body dementia in Portugal. Moreover, we suggest some strategies in order to raise the awareness of physicians, policy makers, and the society at large regarding this disease.